Non-LTE Model Spectra for Gaseous Planetary Debris Disks around WDs. Issue Volume 8:Issue S299(2013) (6th January 2014) - Hartmann, Stephan; Nagel, Thorsten; Rauch, Thomas; Werner, Klaus
Abstract: Metal-rich dust disks around white dwarfs are thought to be the debris of tidally disrupted rocky bodies. While normally the number of features to study the planetary material directly is very limited, ancillary gas disks around some of these white dwarfs provide the opportunity to do so. We used our Tübingen Accretion Disk codeAcDc, assuming non-LTE conditions, to model the gaseous spectrum component. We investigated the chemical mixture as well as the surface density and effective temperature, and utilized the Caii infrared triplet to determine the geometry of the disk.